Pelatihan Pemasaran Online Bagi Mitra UMKM Kerupuk Melarat Di Desa Belendung Karawang Dalam Meningkatkan Penjualan Produk - yuniarsih, yuyun; Irawaty, Sandra; Sanusi, Nunung; Hersusetiyati, Hersusetiyati; Sikki, Nurhaeni; Sabila, Silsi; Firdaus, Ridwan Tho At; Gunawan, Putri Kurnia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Micro, Small and Medium Enterprises play an important role in improving the economy and community welfare. The ability to compete and market products is one of the spearheads so that business actors can exist and be competitive. There are many factors that affect the success of a business, but how a product can dominate the market is one of the priorities that must be done by business actors. In the era of the Industrial Revolution 4.0, business actors can no longer rely on conventional marketing, they must also start marketing their products online. This shift in marketing model must be carried out immediately by business actors so that their products can compete in the global market. Business actors assisted by MSME partners in Karawang have experienced many obstacles in terms of marketing, business actors still rely on conventional marketing and have not utilized social media optimally as a means of marketing their products. The purpose of this activity is to provide knowledge about the use of social media as a marketing medium and provide skills to MSME owners in increasing sales of their products. The methods used in this activity are training and mentoring. The results of the activities besides increasing knowledge are expected that business actors will also be able to take advantage of social media, namely shopee and Instagram as a means of product promotion and marketing so that sales can increase.